2020
DOI: 10.1186/s12864-020-6664-3
|View full text |Cite
|
Sign up to set email alerts
|

Diploid genome differentiation conferred by RNA sequencing-based survey of genome-wide polymorphisms throughout homoeologous loci in Triticum and Aegilops

Abstract: Background: Triticum and Aegilops diploid species have morphological and genetic diversity and are crucial genetic resources for wheat breeding. According to the chromosomal pairing-affinity of these species, their genome nomenclatures have been defined. However, evaluations of genome differentiation based on genomewide nucleotide variations are still limited, especially in the three genomes of the genus Aegilops: Ae. caudata L. (CC genome), Ae. comosa Sibth. et Sm. (MM genome), and Ae. uniaristata Vis. (NN ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…The comparative single-gene FISH analysis highlighted the role of karyotype changes in the evolution of closely related C-, M- and U-genomes of Aegilops . Recent phylogenomic studies on diploid Triticum / Aegilops species using 38 nuclear low copy loci (Huynh et al, 2019 ) and by genome-wide RNA-seq-based polymorphic analysis (Glémin et al, 2019 ; Tanaka et al, 2020 ) have shown that the ancestor of the D-genome lineage went through intensive diversification ~3 Mya, leading to the formation of the current Aegilops species with C, D, M, N, S, and U genomes in the area of Fertile Crescent and their subsequent radiation to the Mediterranean landscapes (Kilian et al, 2011 ). Glémin et al ( 2019 ) and Tanaka et al ( 2020 ) suggested that C-, M-, N-, and U-genome species formed a separated group from those containing the D and S genomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The comparative single-gene FISH analysis highlighted the role of karyotype changes in the evolution of closely related C-, M- and U-genomes of Aegilops . Recent phylogenomic studies on diploid Triticum / Aegilops species using 38 nuclear low copy loci (Huynh et al, 2019 ) and by genome-wide RNA-seq-based polymorphic analysis (Glémin et al, 2019 ; Tanaka et al, 2020 ) have shown that the ancestor of the D-genome lineage went through intensive diversification ~3 Mya, leading to the formation of the current Aegilops species with C, D, M, N, S, and U genomes in the area of Fertile Crescent and their subsequent radiation to the Mediterranean landscapes (Kilian et al, 2011 ). Glémin et al ( 2019 ) and Tanaka et al ( 2020 ) suggested that C-, M-, N-, and U-genome species formed a separated group from those containing the D and S genomes.…”
Section: Discussionmentioning
confidence: 99%
“…comosa and the N genome of Ae. uniaristata (Glémin et al, 2019 ; Tanaka et al, 2020 ). Consistent with these results, the single-gene FISH map of Ae.…”
Section: Discussionmentioning
confidence: 99%
“…comosa (MM genome), and Ae. uniaristata (NN genome) (Tanaka et al 2020). RNA-Seq of these diploid species allowed us to detect genomewide SNPs and indels across chromosomes.…”
Section: Rna-seq Based Dna Marker Analysis Of Other Triticeae Speciesmentioning
confidence: 99%
“…The efficient generation of markers in several Triticeae species prompted us to analyze genome differentiation in diploid wild wheat by applying RNA-Seq to wild wheat species with more diverse diploid genomes. We estimated genome differentiation based on an RNA-Seq-based survey of genome-wide polymorphisms throughout homoeologous loci in Triticum and Aegilops (Tanaka et al (2020). The genome nomenclatures in these species were defined based on their affinity for chromosomal pairing.…”
Section: Umbellulatamentioning
confidence: 99%
See 1 more Smart Citation